UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU - Markis Uriatman (UNIVERSITAS BENGKULU, 2015)
The purpose of this research is to describe the principal’s effort in increasing discipline of teacher of Public Vocational High School in Tugumulyo. The research method was designed as descriptive method. The main source of data was the principal, vise of principal and teachers. The technique of collecting data were interview, observation, and documentations. The results ofanalisis show that the effort of principals in increasing discipline of teacher has the right to do, so that the result is discipline of teacher become quite satisfactory.Keyword: teachers discipline, principal’s effort